Basic reproductive parameters of Kathiawari horses reared under arid zone region - Kumar, Sajjan; Ravi, Sanjay Kumar; Legha, Ram Avtar; Pal, Yash; Talluri, Thirumala (The Indian Journal of Animal Reproduction, 2023)
The current study was undertaken with an aim to record and analyse the data related to basic reproductive parameters such as length of estrus cycle, estrus duration, pre-ovulatory follicle size at ovulation, day of ovulation, length of gestation and days of occurrence of foal heat in respect of Kathiawari mares for a period of thirteen consecutive breeding seasons (2010-2023). The mares were monitored closely for their estrus signs, examined with transrectal ultrasonography for the size of the follicle variation and to determine the size of the follicle at ovulation. The mares were inseminated with the frozen thawed semen collected from Kathiawari stallions at appropriate time. This is the first time ever report that live foals have been obtained using frozen semen via artificial insemination in kathiawari horses. The data on reproductive indices of the mares of Kathiawari breed in India are scanty and there are no available reports on reproductive characteristics of Kathiawari breed until today in the literature. The results of the present findings are of much useful and may serve as a ready reckoner for the reproductive traits of Kathiawari breed reared under arid region. The differences in the reproductive parameters observed in relation to other breeds of Indian horses may be attributed to breed differences and other environmental factors.
Keywords: Arid zone; Estrous cycle; Kathiawari horse; Gestational length; Foal heat